Foot Washing: rituals of body-emotional care for migrants in Mexico’s Bajío region - Rivera Andrade, Samuel Fernando (2025)
In this text we reflect, based on ethnographic data, on the practices of corporal and affective recomposition carried out by the group Amigos del Tren México, a civil association formed by people from different countries and members of a Pentecostal Christian church. This group provides food, personal belongings such as toothbrush and toothpaste, soap, socks and underwear and heals the wounds of the Central American migrant population passing through the city of Irapuato, Guanajuato, Mexico, through the ritual of foot washing. Our interest is focused on analyzing how these practices are embedded in and/or reinforce acts of care for those who are in continuous movement. We found that these practices mitigate part of the consequences that restrictive and security migration policies have left on the bodies and emotions of migrants by exposing them to dangerous and violent transit. We find that learning from these practices strengthens our ethnographic work, as we can integrate part of them into the network of care during ethnographic fieldwork.